Św. Augustyn - duszpasterz (dokończenie) - Eckmann, Augustyn (Vox Patrum, 1988)
In his pastoral service, the saint bishop was zealous love for the God and the man. The great and power, he had been gifted with, did not prevent him close to the people of God, who are also responsible life of the Church.